The Anti-Social Web - Greene, Daniel; Bakioglu, Burcu; Parry, David; Daniels, Jessie (AoIR Selected Papers of Internet Research, 2013)
This panel uses a range of sites and populations to investigate anti-social practices around and within the community spaces of the Web. We focus on how the cultural common sense of an open Web built on sharing is framed against the danger of specific anti-social practices and how practices of openness and sharing rely on anti-social acts for their maintenance. Thus the dominant imaginary of the web as both frictionless free market and anti-hierarchical public sphere has always been positioned against the trolls, bots, and freaks resisting this vision, while practices of censorship, surveillance, and social engineering have been adopted in defense of this vision. These tensions between open sociality, its disruption, and its regulation have been present since the opening of the commercial web in the early- to mid-1990s. US politicians and telecommunications corporations in that period promised that ‘cyberspace’ would be cleared of pornography and theft in order to ensure that it was safe and open for business. The threat of marketing cyberporn to potentially susceptible publics would be met with legislation such as Children’s Internet Protection Act (CIPA), requiring all public access points receiving federal funding to install filtering software on their internet-connected PC’s (Jaeger & Zan, 2009). Simultaneously, MCI advertised cyberspace as an open zone of social and economic relations where bodily markers signifying past social divisions would disappear (e.g., the “Anthem” commercial advertising how online “there is no race”, “there is no gender”). This supported an emergent neoliberal political hegemony where any public insistence on the material effects of racism or sexism were themselves taken to be racist or sexist attacks on the ‘color-blind’ public sphere (Chun, 2006). These discourses circulating on and about the web are thus indicative of a new norm of sociality that takes old ideals of the open, democratic public sphere and repurposes them to support an economic infrastructure based on free flowing but data-mined information (Dean, 2003). Trolls, bots, spammers, porn freaks, and griefers use this open, free-flowing sociality transgressively to serve their own respective agendas and are thus a threat to the dominant political-economic order. The rise of web 2.0 and social networking sites built on user-generated content re-centers the economic imperative of social openness and the political norms of social publicity. Here the profits of websites such as Facebook are always produced through uneven economic relations where users’ free labor becomes profitable data profiles through ubiquitous surveillance–the scope of which is hidden from most users (Anderjevic, 2012). Politically, we see reactions against the anti-social Web overlapping with offline liberal politics; including the way white, middle- and upper-class teenagers, many encouraged by parents, fled from MySpace to Facebook because the former encouraged media experimentation, heavily featured hip-hop culture, and, allegedly was overrun with sexual predators (boyd, 2012). In other words, mid-2000s MySpace was social, but not the right kind of social. The anti-social Web is thus both a set of infrastructural practices shaping a profitable, normative version of Web sociality, and a discourse against which those norms are constructed. The papers in the panel will argue that the anti-social web is not a bug in the system of the social web, but a constitutive feature of that system. To understand LambdaMOO, we must understand Mr. Bungle (Dibbell, 1998, p. 11-33). To understand ‘cyberspace’, we must understand cyberporn. To understand Facebook, we must understand the white flight from MySpace. And to understand Reddit, we must understand Violentacrez (Chen, 2012). This panel explores how the anti-social web exists alongside the social web, as both a set of anti-social practices shaping a normative social space and a set of anti-social figures against which the liberal discourse of the web is defined. [Author’s 1] ethnography of urban public libraries explores how librarians regulate the links between internet access and social mobility, and how library patrons, many of them homeless, refuse those links when they watch porn, sleep, drink, or have sex in the library. [Author 2] explores how griefers’ play has developed hacktivistic undertones and transformed into a strategy for negotiating privacy, transparency, and governance in virtual worlds. [Author 3] examines the phenomenon of ‘cloaked websites’ which hide their white supremacist or pro-life political agendas in order to influence naive Web users. And [Author 4] discusses the anti-democratic potential of ‘big data’ electoral campaigns, which use the data points generated in the putative public sphere of the web to engineer turnout rather than foster broader citizen engagement. With each of these papers, we see the anti-social web shaping the cultural common sense of the open, public social web–whether as a figure to be regulated in the name of norms of democratic publicity, or as a set of anti-democratic practices existing within those same norms. 2 Anderjevic, M. (2012) “Estranged free labor.” In T. Scholz (ed.) 2 (149-164). New York, NY: Routledge. boyd, d. (2011). “White flight in networked publics? How race and class shaped American teen engagement with MySpace and Facebook.” In L. Nakamura & P.A. Chow-White (eds.) 2 (203-222). New York, NY: Routledge. Chen, A. (2012, October 12). Unmasking Reddit’s Violentacrez, the biggest troll on the web. 2 . Retrieved from http://gawker.com/5950981/ Chun, W.H.K. (2008) 2 Cambridge: MIT Press. Dean, J. (2003). Why the net is not a public sphere. 2 10(1), 95-112. Dibbell, J. (1998). 2 New York, NY: Henry Holt and Company. Jaeger, P. T., & Yan, Z. (2009). One law with two outcomes: Comparing the implementation of the Children’s Internet Protection Act in public libraries and public schools. 2 , 28(1), 8-16. MCI, Inc. (1997). “Anthem”. Retrieved at http://www.youtube.com/watch?v=ioVMoeCbrig